A etnotaxonomia dos peixes das vilas, Vista Alegre do Pará e Araticum-Mirim, Marapanim, PA, Brasil - ALVES, Raissa Conceição (2024)
Artisanal fishing is an important socioeconomic activity for the population of the communities present in this study, since their main source of income comes from the fishing trade, the knowledge and experience arising from this activity are important for the identification and classification of natural fish in this region. Taking- this information into account, we sought to delve deeper into the correlation between the common nomenclature used by fishermen and the technical-scientific classification from an ethnobiological perspective. Verifying the vast diversity of ethnospecies in the communities of Northeast Pará, which are called Vista Alegre Do Pará and Araticum-Mirim located in Marapanim-Pa. To obtain information, interviews were carried out with fishermen/residents of the regions, covering the name, profession, age and mainly the popular name of each species captured. Interviews were carried out with six local fishermen, all male, aged between 30 and 59 years old. Species-level records were carried out in 36 taxa, distributed in 18 families and 14 different orders. These data arise from 13 ethnospecies recorded in Araticum and 25 ethnospecies recorded in Vista Alegre do Pará.